Success of Wildlife Disease Treatment Depends on Host Immune Response - Maslo, Brooke; Gignoux-Wolfsohn, Sarah A.; Fefferman, Nina H. (Frontiers in Ecology and Evolution, 2017)
Infectious diseases significantly threaten many wildlife populations. Proposed treatments often fail to consider resulting impacts on natural host defense mechanisms and ongoing infection risks. We demonstrate the importance of prior knowledge of host defenses by modeling outcomes of various treatment regimes on bat populations infected with white-nose syndrome (WNS), a disease that has caused declines in multiple North American species. Despite differences in species susceptibility to the causative fungus, how hosts respond to and survive infection remains unclear. We explore three potential host-defense mechanisms: upregulation of the responsive innate or adaptive immune systems, and rapid evolution that enables evolutionary rescue. We demonstrate that treatment can accelerate extirpation (relative to inaction) if hosts are defended by responsive immunity; whereas, treatment can cause populations undergoing evolutionary rescue to regain population viability faster. We conclude that successful treatment of wildlife diseases must first consider how individuals respond to and survive infection.